A Tibetan Verb Lexicon SecondEdition, Updated and Expanded - Altenburg, Gerjan (Canadian Journal of Buddhist Studies, 2023)
PAUL G. HACKETT, A Tibetan Verb Lexicon (Second Edition, Updated and Expanded). Boulder: Snow Lion Publications, 2019. Xii, 507 pp. US $49.95 (pb). ISBN 9781559394833,